Rheology of liquid formulations and searching for eco-friendly thickeners - Soh, Wendy Yun Zheng (Nanyang Technological University, 2023)
This report describes a project that involves creating a dataset of formulations to develop a model capable of predicting the properties of liquid formulations, with a focus on shampoo formulations. The aim is to accelerate research and development cycles and explore sustainable ingredient alternatives, particularly for thickeners used in shampoos. The surfactants used and the shampoo samples formulated are tested using a rotational rheometer, and the rheology properties are plotted on a log viscosity against a log shear rate graph. Using the power law model, the graphs can be evaluated as Newtonian or non-Newtonian. The report also discusses traditional and common thickener ingredients used in shampoo formulations, ways to source alternative ingredients using life cycle assessment and feasibility tests, and methods to produce more sustainable ingredients, such as bio-fermentation. Sustainable alternative ingredients to current thickeners will be listed, such as chitosan, cellulose, carrageenan, hyaluronic acid, and alginate.